Depth-related plasticity in the diet composition of Pseudechinus magellanicus (Echinoidea, Temnopleuridae) in nearshore environments off central Patagonia, Argentina - Gil, Damián Gaspar (2021)
Pseudechinus magellanicus is one of the most abundant sea urchins in southern South America, but many aspects of its feeding ecology in nearshore environments remain unknown. Here, we aimed to analyze the variability of the diet composition along a coastal depth gradient from intertidal tidepools to upper circalittoral zones and examine the relation between seaweed availability and the diet composition at intertidal tidepools. A total of 118 food items, including seaweeds and animal components, were identified. The diet composition showed a large variation between the different coastal habitats present along the depth gradient studied. In tidepools, articulate coralline seaweeds (Corallina spp.), mussel shell fragments and small crustaceans were frequent in the gut contents, suggesting that this species behaves like a general omnivore but can also act as a mussel bioeroder when consuming epizoic algae and microeuendolithic organisms. In intertidal tidepools, the species showed a negative preference toward typical species of late successional stages such as Dictyota dichotoma, Adenocystis utricularis, Codium fragile and Chondria macrocarpa. Sea urchins from kelp forests showed higher dietary diversity than those from intertidal and deeper subtidal habitats, but with prevalence of kelps. At upper circalittoral soft bottoms, diverse detrital items as benthic diatoms, cyanobacteria and drifted algae were observed in gut contents, usually associated with fine sediments, indicating that P. magellanicus captures drifted algae and behaves like a biofilm feeder. This trophic plasticity may allow this species to occupy contrasting habitats and may also contribute to explain its wide distribution in southern South America.